2012
DOI: 10.1002/mc.21970
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole intervention of breast cell carcinogenesis

Abstract: Dietary prevention is a cost-efficient strategy to reduce the risk of human cancers. More than 85% breast cancers are sporadic and attributable to long-term exposure to environmental carcinogens through a multistep and multiyear disease process. We used our chronically induced cellular carcinogenesis model as a target to search for preventive agents capable of blocking breast cell carcinogenesis. Dipyridamole (DPM), at a non-cytotoxic physiologically achievable dose of 10  nmol/L, effectively blocked breast ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Another study showed mild down-regulation of Bcl2 and extremely significant up regular of Bax in solid Ehrlich carcinoma-bearing mice. In our studies, dipyridamole made overexpression for CYC gene in 231 cell line as in anther studies dipyridamole increased intracellular c-AMP and inhibited Erk1/2 activation in of human peritoneal mesothelial cell proliferation (Padala et al, 2017;Choudhary et al, 2014). Some studies suggested that DIM possesses beneficial properties, either direct or indirect effects, such as downstream effects on cell signalling proliferation inhibition, anti-inflammatory and antioxidant properties (Sureechatchaiyan et al, 2018).…”
Section: Discussionmentioning
confidence: 55%
“…Another study showed mild down-regulation of Bcl2 and extremely significant up regular of Bax in solid Ehrlich carcinoma-bearing mice. In our studies, dipyridamole made overexpression for CYC gene in 231 cell line as in anther studies dipyridamole increased intracellular c-AMP and inhibited Erk1/2 activation in of human peritoneal mesothelial cell proliferation (Padala et al, 2017;Choudhary et al, 2014). Some studies suggested that DIM possesses beneficial properties, either direct or indirect effects, such as downstream effects on cell signalling proliferation inhibition, anti-inflammatory and antioxidant properties (Sureechatchaiyan et al, 2018).…”
Section: Discussionmentioning
confidence: 55%
“…These observations, as well as our finding in this study that PDE8A is prominently expressed at the mRNA level in all breast cancer cells and tissues examined, and the recent finding that PDE8A binds to and regulates raf-1 [31], which controls many fundamental biological processes, suggests that PDE8A may provide an excellent novel target for inhibiting breast cancer metastasis. Of note, the nonselective PDE inhibitor, dipyridamole, which in contrast to the nonselective methylxanthine PDE inhibitors, is capable of inhibiting PDE8A, and which we show to significantly inhibit breast cancer cell migration, was recently shown to inhibit breast cancer tumorigenesis and metastasis in animal models [59][60][61], further suggesting that PDE8A may represent an excellent new target for breast cancer treatment.…”
Section: Discussionmentioning
confidence: 60%
“…Emerging evidence, in vitro and in vivo, has shown an anti-cancer effect of dipyridamole via its anti-viral activity, immunoregulation, autophagic flux blockade, anti-proliferative activity, inhibiting tumour cell metastasis, and its enhancing the cytotoxicity of anti-cancer drugs. [8][9][10][11][12][13][14][15][16] The anti-cancer effects of dipyridamole are mainly involved in PDE inhibitions, including PDE10, PDE8, PDE5, and PDE4. 1,2 Growing evidence suggests that PDEs play an important role in carcinogenesis via influencing the level of cAMP and/or cGMP; thus, PDEs have the potential to be a novel target for inhibiting tumour cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Recently, a growing amount of evidence from preclinical research indicated the anti-cancer activity of dipyridamole on several types of malignancies, including colorectal, breast, prostate, or haematological malignancies. [8][9][10][11][12][13][14][15][16] Dipyridamole was recently found to prevent Epstein-Barr virus (EBV) re-activation, indicating a possibility to be repurposed as a nontoxic anti-viral drug to prevent EBV-related diseases. 10 It is known that EBV was originally discovered in cells from Burkitt's lymphoma, and the re-activation has been demonstrated to directly and indirectly associate with lymphomagenesis.…”
Section: Introductionmentioning
confidence: 99%